The acquired and required competencies of Pakistani university librarians: Determining the job satisfaction, organizational commitment and training needs / Asad Khan - Khan, Asad (2015)
Modern innovations have enhanced the significance of competent, satisfied and committed workforce. However, these innovations have caused numerous potential challenges for university librarians. University librarians are expected to be highly competent, satisfied and committed employees to serve users in their information needs. However, previous researchers indicated that acquired skills of Pakistani university librarians are not matching with modern professional demands. This has given birth to numerous questions, such as ineffective performance, poor attitude of university librarians towards the attainment of required skills, negligence of professional values, compatibility between LIS curriculum and job market, perplexing levels of satisfaction and commitment of librarians, limited training opportunities due to undefined areas of required skills etc. Modern librarianship demands university librarians to achieve high level of skills under different areas such as emotional intelligence, cognitive abilities, leadership, communication, collection management and technology management. Thus, in the perspective of Pakistani university librarians, the current exploratory study examines; 1) association of acquired competencies with job satisfaction and organizational commitment; 2) difference between the acquired and required competencies that further prompted to training needs assessment. The present research study employed cross-sectional survey methodology involving 225 samples, randomly selected from the population of 540 Pakistani university librarians. The survey response rate was calculated as 82%. The UniLIBCQ, as structured questionnaire was utilized to collect data on acquired and required competencies, job satisfaction and organizational commitment of Pakistani university librarians. The psychometric properties of UniLIBCQ were established through Cronbach alpha and exploratory factor analysis. In terms of Pakistani university librarians, descriptive analysis indicated that perceived and desired levels of acquired and required competencies are moderate. Based on findings of correlation analysis, all six variables are positively and significantly correlated with JS and OC. Similarly, regression analysis showed that all acquired competencies have significantly predicted JS and OC and thus all research hypotheses (H1-H12) are supported. Further, stepwise multiple regression analysis showed emotional intelligence and collection management competencies as the strongest predictors of JS and OC. Further, findings of the paired sample t-test showed that difference between all dimensions is significant, however in terms of resource sharing are insignificant. Thus, fifteen hypotheses are supported, while one is rejected (H24). Additionally, training needs analysis determined that less than fifty percent of librarians need training to enhance their current level of skills. In Pakistani perspective this study was the first attempt to investigate empirically the theoretical links of competencies with job satisfaction and organizational commitment. In addition, this study is significant as it explored certain training areas. The concerned Pakistani authorities may organize training programs for university librarians to manage gaps in the levels of acquired and required competencies. It may further prompt to high levels of satisfaction and commitment because findings indicated a positive and significant association between the study constructs. It is established that competencies, JS and OC are three important variables that positively and significantly affect workers' performance. The findings of this study are also significant for other organizations that are interested to enhance workers' performance trough JS and OC. It is concluded that enhancing level of competencies may produce highly satisfied and committed librarians and probably augment their performance.